Protein Kinase B/Akt Phosphorylates and Inhibits the Cardiac Na+/H+ Exchanger NHE1 - Snabaitis, Andrew K.; Cuello, Friederike; Avkiran, Metin (Circulation research, 2008)
Sarcolemmal Na/H exchanger (NHE) activity is mediated by NHE isoform 1 (NHE1), which is subject to regulation by protein kinases. Our objectives were to determine whether NHE1 is phosphorylated by protein kinase B (PKB), identify any pertinent phosphorylation site(s), and delineate the functional consequences of such phosphorylation. Active PKBα phosphorylated in vitro a glutathione S-transferase (GST)-NHE1 fusion protein comprising amino acids 516 to 815 of the NHE1 carboxyl-terminal regulatory domain. PKBα-mediated phosphorylation of GST-NHE1 fusion proteins containing overlapping segments of this region localized the targeted residues to the carboxyl-terminal 190 amino acids (625 to 815) of NHE1. Mass spectrometry and phosphorylation analysis of mutated (Ser→Ala) GST-NHE1 fusion proteins revealed that PKBα-mediated phosphorylation of NHE1 occurred principally at Ser648. Far-Western assays demonstrated that PKBα-mediated Ser648 phosphorylation abrogated calcium-activated calmodulin (CaM) binding to the regulatory domain of NHE1. In adult rat ventricular myocytes, adenovirus-mediated expression of myristoylated PKBα (myr-PKBα) increased cellular PKB activity, as confirmed by increased glycogen synthase kinase 3β phosphorylation. Heterologously expressed myr-PKBα was present in the sarcolemma, colocalized with NHE1 at the intercalated disc regions, increased NHE1 phosphorylation, and reduced NHE1 activity following intracellular acidosis. Conversely, pharmacological inhibition of endogenous PKB increased NHE1 activity following intracellular acidosis. Our data suggest that NHE1 is a novel PKB substrate and that its PKB-mediated phosphorylation at Ser648 inhibits sarcolemmal NHE activity during intracellular acidosis, most likely by interfering with CaM binding and reducing affinity for intracellular H.